2019
DOI: 10.1109/access.2019.2952362
|View full text |Cite
|
Sign up to set email alerts
|

Proactive Resilience of Power Systems Against Natural Disasters: A Literature Review

Abstract: The increase in power outages caused by high-impact low-probability events, such as extreme weather-related climate variation events, is the main reason behind studying power system resilience. However, the concepts of resilience as well as the proactive procedures that can be carried out to address these events are such have not so far been satisfactorily investigated notwithstanding their growing benefits. This paper exhibits a review of the current research on power system resilience; which predominantly fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(80 citation statements)
references
References 137 publications
(109 reference statements)
1
60
0
1
Order By: Relevance
“…These power outages occur for a variety of reasons, that range from natural events to intentional attacks on the power supply. A recent paper found that between 2012 and 2016, over 96.2% of power outages occurred due to the impact of severe weather [2] on transmission, and to a greater extent, on distribution networks [3]. Storms and hurricanes account for the vast majority of these outages.…”
Section: Indices Tmentioning
confidence: 99%
See 3 more Smart Citations
“…These power outages occur for a variety of reasons, that range from natural events to intentional attacks on the power supply. A recent paper found that between 2012 and 2016, over 96.2% of power outages occurred due to the impact of severe weather [2] on transmission, and to a greater extent, on distribution networks [3]. Storms and hurricanes account for the vast majority of these outages.…”
Section: Indices Tmentioning
confidence: 99%
“…Storms and hurricanes account for the vast majority of these outages. Resilience of a system can be defined as its ability to prepare, predict, sustain and recover from an outage [3]. This definition is applicable to the power system as a whole or one of its components, such as a household.…”
Section: Indices Tmentioning
confidence: 99%
See 2 more Smart Citations
“…The uncertainty at different stages of PLS, PRS and ERS is another critical factor affecting the MEG planning strategies [22]. Generally, based on the stage of uncertainty realization, the uncertainty to be considered in the resilience-oriented planning can be categorized to intensity uncertainty (IU) of different natural disasters and outage uncertainty (OU) incurred by a given natural disaster [23].…”
Section: Introductionmentioning
confidence: 99%